Relationship between anemia and circulating levels of amino acids in female endurance athletes - Momma, R.; Kumagai, H.; Oshiden, M.; Iemitsu, M.; Maeda, S. (Japanese Journal of Physical Fitness and Sports Medicine, 2017)
The symptoms of anemia, decreases in the levels of circulating red blood cells (RBC), hemoglobin (Hb) and hematocrit (Ht) lead to decrease endurance performance, and the risk of anemia increases in female endurance athletes. Although Hb is composed of a large amount of amino acids, the relationships between circulating levels of amino acids and RBC, Hb and Ht in female endurance athletes have not been clarified yet. Thus, the purpose of the present study was to investigate the relationship between circulating levels of amino acids and RBC, Hb and Ht in female endurance athletes. Twenty-four female endurance athletes (19.8 ± 0.2 years) participated in this study. We measured circulating levels of RBC, Hb and Ht from blood. Also, we measured circulating levels of amino acids from plasma by use of comprehensive analysis. The levels of circulating RBC, Hb and Ht in all subjects were within the normal range. We found that circulating taurine levels were significantly correlated with RBC (r = 0.48, p < 0.05), Hb (r = 0.44, p < 0.05) and Ht (r = 0.42, p < 0.05) in female endurance athletes. In the present study, we demonstrated that circulating taurine levels were significantly associated with RBC, Hb and Ht in female endurance athletes. These results suggest that circulating taurine levels may be a predictor of anemia and treatment strategy for anemia.